(untitled) (Journal of the College of Basic Education, 2026)
The research aims to shed light on linguistic elements, whether textual or extratextual, as they are an important driver of coherence. Coherence may be viewed as inherent in the text, a view that is highly accurate, as the Qur’anic text possesses elements of coherence and its potential, ranging from formulas and structures to semantics. Coherence may also exist outside the text, meaning that the recipient is the one who judges a text to be coherent. The elements of textual interaction are not hidden from us, as they are not related to the text alone, but rather extend beyond it to its recipient, sender, context, and all elements of the communication process. The text, with its contents and interacting elements, generates internal harmony, and the recipient, with his culture and thought, qualifies him to interact with this or that text in different ways, in addition to the role of the context and the rest of the elements of the communication process in this interaction between the text and the recipient, from which harmony is generated between the two parties. Therefore, the internal or external textual interaction was the result of the general harmony in the entire communication process, especially between the text and its recipient. Due to the narrow scope of the research, we adhered to selected models, and the research relied on the descriptive and analytical approaches